1995
DOI: 10.1126/science.270.5241.1480
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Organization of Surfactants at Solid-Liquid Interfaces

Abstract: Interactions between surfactant solutions and solid surfaces play a key role in technologically important processes such as colloidal stabilization, ore flotation, and soil removal; however, the interfacial aggregation of surfactant molecules is not yet well understood. Direct images of surfactant aggregates at solid surfaces in aqueous solutions were obtained with atomic force microscopy. The resulting structures for quaternary ammonium surfactants (above the critical micelle concentration) are consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

72
701
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 690 publications
(775 citation statements)
references
References 33 publications
72
701
1
1
Order By: Relevance
“…The aggregates of many commonly studied surfactants on smooth surfaces are close-packed micelles of cylindrical, hemicylindrical, or spherical shape with typical center-to-center distances of 5-7 nm. 36 We aim to estimate the influence of the size of the AFM probe on the obtained image of such samples, which proves relatively difficult. The micellar aggregates are soft structures that are removed from the surface by energies as little as 10-20 kJ/ mol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aggregates of many commonly studied surfactants on smooth surfaces are close-packed micelles of cylindrical, hemicylindrical, or spherical shape with typical center-to-center distances of 5-7 nm. 36 We aim to estimate the influence of the size of the AFM probe on the obtained image of such samples, which proves relatively difficult. The micellar aggregates are soft structures that are removed from the surface by energies as little as 10-20 kJ/ mol.…”
Section: Resultsmentioning
confidence: 99%
“…35,36 Pioneered by Manne and co-workers, this technique revealed that surfactants form surface aggregates in the shape of full 36 or half [35][36][37][38] cylinders or full 36 or half 39 spheres, as well as flat layers, 36,40 depending on the system under investigation. These findings have been confirmed by computational investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, surfactant adsorption and the resulting surface structures have been studied by various experimental techniques such as the streaming potential method, 3 calorimetry, 4 neutron reflection, 5-7 ellipsometry [8][9][10] and fluorescence spectroscopy, 11,12 and atomic force microscopy (AFM). [13][14][15][16][17][18][19][20][21] Of these, AFM provides the most detailed information on the topology of the assembled surfactant structures at molecular scales: Manne et al first provided evidence of hexadecyltrimethylammonium bromide (C 16 TAB) organization in parallel stripes at the interface between graphite and aqueous solution. 17 In subsequent studies, similar morphologies have been observed for various other surfactants and hydrophobic surfaces, 13,18,20 among them sodium dodecyl sulfate (SDS) on graphite.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorbed stripes were generally observed in three orientations. Based on observations like these Manne et al [734,793] concluded that CTAB forms cylindrical hemimicelles on graphite (HOPG), full cylinders on mica and spherical micelles on silica. Meanwhile the structure of several surfactants on various surfaces has been revealed.…”
Section: Adsorbed Surfactantsmentioning
confidence: 99%